The use of Programming Tools in Teaching and Learning Material by K-12 Teachers - Humble, Niklas (Proceedings of the ... European conference on e-learning (Online), 2021)
The integration of programming in K-12 education (kindergarten to grade 12) can be viewed worldwide. Expected outcomes of the integration is that students will develop skills in problem solving, creativity, logical thinking, reasoning, and computational thinking. Previous research has identified several challenges for the integration of programming, such as lack of guidance, motivation, time and competence. The aim of this study is to examine the use of programming tools in teaching and learning material by K-12 teachers. The teaching and learning material analysed in this study were collected from a website (Lektion.se) where K-12 teachers can share their teaching and learning material with each other. A document review process, inspired by a systematic literature review process, was used to select the teaching and learning material to be included in the study. The selected teaching and learning material were later analysed through content analysis with deductive and inductive coding. In the study, four types of programming tools can be found in the analysed teaching and learning material: textual programming tools, block programming tools, tangible programming tools, and unplugged programming. The findings of the study indicate potential relationships between the use of different programming tools and school subjects and student grades. These findings can be drawn upon by teachers and other stakeholders in the decision on what programming tools to integrate in classroom practice and how they are to be used.